Educação musical na cuica: percussões e repercussões de um projeto social - Rozzini, José Everton da Silva (2012)
This present work was developed in the Line of Research Education and Arts (LP4) of the Post Graduation in Education Program of the Federal University of Santa Maria (UFSM) and binds to the group of studies and researches FAPEM - Training, Action and Research in Music Education of UFSM. The research had as a general purpose to investigate the repercussions of the CUICA Association in the lives of four young percussionists participants in the percussion group CUICA, through their narratives. As the specific objectives it sought to understand how to learn music in CUICA Association through the practice of percussion as the axis of the work. It also sought to understand how the musical experiences in CUICA affects and have repercussion to the lives of its participants and reflect how these musical experiences enter and go through to their lives. For this, literature review was consisted of authors who discuss about social education and social projects such as OLIVEIRA (2003); KATER (2004); KLEBER (2003, 2006, 2008); PAIVA (2004); GUAZINA (2011); among others. The research also was supported by theoretical studies on experiences of DEWEY (1959, 2003, 2011); LARROSA BONÍA (2002), JOSSO (2010), that allowed to reflect on the experiences. Methodologically the research developed by the qualitative method, through narrative interviews KVALE, 1994; (BAUER and GASKELL, 2002; FLICK, 2009; CRESWEL, 2010). In this process of investigation it was possible to identify the main musical experiences and some of these repercussions in the lives of participants. It was found that the four young people surveyed have an intense life in CUICA and, consequently, several experiences that result from their participation in the percussion group and go through their lives. Today, the four young people are working with music professionally and express their desire to continue studying music.